Integrated AVO inversion and seismic attributes for tracing hydrocarbon accumulation in Kafr El-Sheikh Formation, South Batra field, Nile Delta, Egypt: A case study - GOBASHY, Mohamed Mostafa; DAHROUG, Aia Mohamed Fathy; ZAKARIA, Ahmed Hussein; SALAHELDIN, Amr Mohamed; SHARAFELDIN, Sharafeldin Mahmoud (Contributions to Geophysics and Geodesy, 2022)
Utilizing advanced seismic techniques for delineating hydrocarbon accumulations in HST (High Stand System Tract) turbidite channel of Kafr El-Sheikh (KS) formation (Pliocene Age) located in the western part of South Batra field (SBF), Nile Delta – Egypt is investigated. 3D seismic data and four well logs helped in studying the properties of the channel. Three wells encountered the central part of the channel and showed thicker reservoir thickness than the fourth well, which encountered the levee. The channel is characterized by high porosity (25–30%) and relatively low water saturation (27–50%). The structural map showed that the channel is dipping towards the NE–SW. AVO analysis, scaled Poisson’s ratio, post-stack seismic inversion, and seismic attributes confirmed the presence of Class III gas sand. Variance attribute helped in imaging the channel and faults. Maps generated from spectral decomposition showed that the dominant frequency is around 15 hertz. Results of integrating different techniques were consistent and successfully helped in determining the geometry of the channel, discriminating between different lithologies and fluids, in addition to delineating the sweet spots and recommended locations for drilling.